2011
DOI: 10.4103/2229-5178.85998
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric reticulohistiocytosis

Abstract: Multicentric reticulohistiocytosis is a rare systemic granulomatous disease of an unknown cause, characterized by distinct histopathology. The skin, mucosa, synovial, bone, and internal organs may be involved. Cutaneous nodules and distinctive arthritis are the most prominent clinical features. A 55-year-old female was referred from Orthopedic Outpatient Department, with multiple, painful and tender nodules on the dorsum of her hands, forearms, elbows, back, and neck. The lesions were present predominantly aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The finding of dermal infiltration of mononuclear and multinucleated giant cells with eosinophilic "ground glass" PAS positive cytoplasm is typical of MRH [15]. These cells are positive for TRAP, CD68, lysozyme and human alveolar macrophage-56 (HAM-56) whereas negative for S100protein, CD1a and factor XIIIa [3]. However it is noteworthy to mention that Bialy Nicki-B R et al [7] had observed S100 positivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding of dermal infiltration of mononuclear and multinucleated giant cells with eosinophilic "ground glass" PAS positive cytoplasm is typical of MRH [15]. These cells are positive for TRAP, CD68, lysozyme and human alveolar macrophage-56 (HAM-56) whereas negative for S100protein, CD1a and factor XIIIa [3]. However it is noteworthy to mention that Bialy Nicki-B R et al [7] had observed S100 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…While inflammatory joint disease is a frequent presenting symptom, and is sole symptom in 45% of patients, skin disease is the presenting manifestation in 30% of patients [10]. Arthropathy usually precedes skin lesions (50%); skin lesions may precede disease (25%) or both can occur concurrently (25%) [3]. It manifests with diffuse, symmetric, progressive and destructive polyarthritis affecting interphalangeal joints mainly the distal interphalangeal joints (75%) and other joints like knees, wrists, shoulders and elbows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin involvement generally establishes with translucent reddish-brown to flesh-colored papulonodules varying from 1-2 mm to 1 cm in diameter or larger. In MRH, papulonodular skin lesions are often associated with arthritis [2].…”
Section: Introductionmentioning
confidence: 99%